SECURITY ROUTING SIMULATION THE LOCAL AREA NETWORK OF ACADEMIC DEPARTMENTS USING A LINK-STATE ROUTING PROTOCOL - OSPF: SECURITY ROUTING SIMULATION THE LOCAL AREA NETWORK OF ACADEMIC DEPARTMENTS USING A LINK-STATE ROUTING PROTOCOL - OSPF - Boyanov, Petar; Stoyanov, Stiliyan; Hristov, Hristo; Fetfov, Ognyan; Trifonov, Tihomir (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a summarized simulation and providing security communication in the local area network of academic department using a link-state routing protocol - OSPF is made. Most of the professional system administrators and IT specialists have to use and apply static and dynamic methods of information routing. Thereby, each network system administrators, security professionals and network architects can use the free of charge software network program Cisco Packet Tracer in order to design and simulate various types of computer networks.